NGM282 for Treatment of Patients With Primary Biliary Cholangitis: A Multicenter, Randomized, Double‐Blind, Placebo‐Controlled Trial. Issue 9 (30th August 2018) - Mayo, Marlyn J.; Wigg, Alan J.; Leggett, Barbara A.; Arnold, Hays; Thompson, Alexander J.; Weltman, Martin; Carey, Elizabeth J.; Muir, Andrew J.; Ling, Lei; Rossi, Stephen J.; DePaoli, Alex M.
Abstract : Patients with primary biliary cholangitis (PBC) who had an inadequate response to ursodiol have few treatment options. Alkaline phosphatase (ALP) and bilirubin levels correlate with the risk of liver transplant or death in PBC patients. Fibroblast growth factor (FGF) 19 is a hormone that acts directly in the liver to regulate bile acid synthesis. We evaluated NGM282, an engineered analogue of FGF19, for the treatment of PBC. In this 28‐day, double‐blind, placebo‐controlled phase 2 trial, 45 PBC patients who had an inadequate response to ursodiol were randomly assigned 1:1:1 to receive subcutaneous daily doses of either NGM282 at 0.3 mg (n = 14), 3 mg (n = 16), or placebo (n = 15). The primary endpoint was a change in ALP from baseline after 28 days of treatment. At day 28, ALP was significantly reduced with NGM282 treatment at both 0.3 mg (least‐squares mean –51.0 IU/L [standard error (SE) 15.4]) and 3 mg (–66.0 IU/L [SE 16.0]) versus placebo (3.3 IU/L [SE 14.8]), with least‐squares mean differences of –54.3 IU/L (95% confidence interval –104.2 to –4.5; P = 0.0149) and –69.3 IU/L (95% confidence interval –120.5 to –18.3; P = 0.0030), respectively. Fifty percent (7 of 14) of patients receiving NGM282 0.3 mg and 46% (6 of 13) of those receiving NGM282 3mg achieved 15% or greater reduction in ALP levels from baseline, compared with 7% (1 of 15) of patients receiving placebo. NGM282 also significantly reduced serum concentrations of transaminases and immunoglobulins. Most adverse events were grade 1 (mild) to grade 2 (moderate) in severity, with gastrointestinal disorders more frequent in the NGM282 treatment groups. No worsening of pruritus was observed with NGM282 treatment. Conclusion: NGM282 administered for 28 days resulted in significant improvements in ALP and transaminase levels compared with placebo, with an acceptable safety profile in patients with PBC. ( Hepatology Communications 2018; 00:000‐000) Abstract : NGM282 administered for 28 days resulted in significant improvements in ALP and transaminase levels compared with placebo, with an acceptable safety profile in patients with primary biliary cholangitis.